Development of discourse-pragmatic markers in a multilingual classroom: A mixed method research approach. (July 2018) - Martín-Laguna, Sofía; Alcón-Soler, Eva
Abstract: Research has shown that being multilingual is a valuable asset for learning pragmatics. By adopting a multilingual turn perspective, this study investigates patterns of pragmatic development in the multilingual classroom setting of the Valencian Community in Spain, where English, Catalan and Spanish coexist. Participants were 313 learners of English and 15 teachers. Each learner wrote three argumentative essays over one academic year in three languages: English, Catalan and Spanish. A mixed method approach was followed to examine learning trajectories of two types of discourse-pragmatic markers: textual and interpersonal markers. Quantitative results revealed significant gains in the production of textual discourse-pragmatic markers in English, while interpersonal discourse-pragmatic markers followed an irregular pattern. Findings also revealed variations in discourse-pragmatic marker learning trajectories in English, Catalan and Spanish: learning trajectories in the minority language (Catalan) and the L3 (English) were more fluctuating and the patterns interacted with each other, which contrasted with the linear development found in the majority language (Spanish). Qualitative findings are discussed to illustrate how factors such as learners' pragmatic awareness, teachers' practices and the sociolinguistic context of the study may interact in the process of pragmatic learning in the multilingual classroom.